2021
DOI: 10.1038/s41419-021-04054-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: the potential value target in atherosclerosis

Abstract: In advanced atherosclerosis (AS), defective function-induced cell death leads to the formation of the characteristic necrotic core and vulnerable plaque. The forms and mechanisms of cell death in AS have recently been elucidated. Among them, ferroptosis, an iron-dependent form of necrosis that is characterized by oxidative damage to phospholipids, promotes AS by accelerating endothelial dysfunction in lipid peroxidation. Moreover, disordered intracellular iron causes damage to macrophages, vascular smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 110 publications
(152 reference statements)
0
65
0
1
Order By: Relevance
“…Depletion of the antioxidant GSH or ox-LDL lead to the accumulation of intracellular lipid peroxide ( Dixon et al, 2012 ; Kattoor et al, 2017 ; Ouyang et al, 2021 ). Over-expression of GPX4 in ApoE −/− mice attenuates the upregulation of endothelial cell adhesion molecule and monocyte-endothelial cell adhesion, thereby inhibiting the development of AS ( Guo et al, 2008 ).…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…Depletion of the antioxidant GSH or ox-LDL lead to the accumulation of intracellular lipid peroxide ( Dixon et al, 2012 ; Kattoor et al, 2017 ; Ouyang et al, 2021 ). Over-expression of GPX4 in ApoE −/− mice attenuates the upregulation of endothelial cell adhesion molecule and monocyte-endothelial cell adhesion, thereby inhibiting the development of AS ( Guo et al, 2008 ).…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
“…12/15-LOX promotes increased trans-endothelial transport of ox-LDL and deposition of ox-LDL in the sub-endothelial space ( Li et al, 2018 ). ALOX12 exhibits higher methylation levels in atherosclerotic plaques, particularly in endothelial cells, which is essential for p53-mediated ferroptosis following stress ( Ouyang et al, 2021 ). The p53 gene also promotes ferroptosis through histone modification with non-dependent of p53 ( Dai et al, 2020 ).…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that when ferroptosis occurs in neurons, then microglia are activated and release toxic substances including pro-inflammatory factor IL-6, which can cause neuro-inflammation and lead to further brain damage ( Tang et al, 2020 ). In addition, ferroptosis also changes the inflammatory phenotype in macrophages ( Ouyang et al, 2021 ), which promotes macrophage polarization and then aggravates inflammation ( Yu et al, 2021 ). Ferroptosis is capable of directly releasing the pro-inflammatory damaged-associated molecular patterns (DAMPs) that promote the development of inflammation and numerous inflammatory diseases.…”
Section: The Mechanism Of Ferroptosismentioning
confidence: 99%